PERAN PENDIDIKAN AGAMA ISLAM DALAM KELUARGA DAN MASYARAKAT - Djaelani, Moh.Solikodin (Jurnal Ilmiah Widya, 2013)
Education in the family is an important aspect in the formation of a person's behavior. Usually in the family instilled religious values and ethic. The aim of this writing is to discuss the role of religious education in the family and society. This method used libriary research with the descriptive and explorative approach.. The conclusions are that: (1) the role of the Islamic education are as the foundation of religious education in a family which used to form the children’ good attitude and behavior, (2) functions as tools to convince people to the almighty God, (3) in community the Islamic education plays an important role as a foundation to build the society character for the Indonesian people to improve the nation.